Validation of the Chinese version of Emotion Regulation Strategies for Artistic Creative Activities Scale (ERS-ACA-C) among Chinese college students majoring in art and design - Yu, Aifang; Shi, Zhidao (Frontiers in Psychology, 2025)
AimTranslating the Emotion Regulation Strategies for Artistic Creative Activities Scale (ERS-ACA) into Chinese and adapting it for Chinese college students majoring in art and design.MethodsTranslated ERS-ACA into Chinese using a cross-cultural adaptation approach, and validated its psychometric properties among Chinese college students majoring in art and design. Three hundred and thirty-eight Chinese college students majoring in art and design were collected to test the scale’s reliability and validity, of which 150 students were retested 2 weeks later. Another 200 college students majoring in art and design were selected to perform Confirmatory Factor Analysis (CFA).ResultsItem 1 of the Chinese version of ERS-ACA (ERS-ACA-C) was removed for its low correlation with the total score of ERS-ACA-C. We got the ERS-ACA-C with 17 items. Exploratory Factor Analysis (EFA) revealed that ERS-ACA-C has a general factor and three factors, consisting of 17 items. The explained variance of ERS-ACA-C was 61.098%. CFA validated that the three-factor model fit the data of ERS-ACA-C. The Cronbach’s alpha coefficient of ERS-ACA-C and its three factors was 0.883, 0.857, 0.875, and 0.854, respectively. Correlation analysis was performed between ERS-ACA-C and Self-Expression and Emotion Regulation in Art Making Scale (SERAMS) to calculate the criterion-related validity (r = 0.721, p < 0.001). The correlation coefficient r of the ERS-ACA-C’s test–retest reliability was 0.902 (p < 0.001). ERS-ACA-C’s split-half reliability was 0.754 (Spearman-Brown coefficient).ConclusionERS-ACA-C has relatively good reliability and validity. It can be used to assess the Emotion Regulation Strategies for Artistic Creative Activities of Chinese college students majoring in art and design in their artistic creative activities.